2021
DOI: 10.1111/jop.13227
|View full text |Cite
|
Sign up to set email alerts
|

Automatic classification and detection of oral cancer in photographic images using deep learning algorithms

Abstract: Background Oral cancer is a deadly disease among the most common malignant tumors worldwide, and it has become an increasingly important public health problem in developing and low‐to‐middle income countries. This study aims to use the convolutional neural network (CNN) deep learning algorithms to develop an automated classification and detection model for oral cancer screening. Methods The study included 700 clinical oral photographs, collected retrospectively from the oral and maxillofacial center, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 27 publications
0
54
0
2
Order By: Relevance
“…This analysis included 14 studies [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Table 1 presents the assessment of bias.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This analysis included 14 studies [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Table 1 presents the assessment of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Since its introduction in 1991 [ 36 ], OCT has been developed to provide high-resolution images at a faster speed and has played an important role in the biomedical field. In an AI analysis study of OCT images published by Yang et al, it was reported that the sensitivity and specificity of oral cancer diagnosis was 98% or more [ 22 ]. In our study, OCT images were found to be the most accurate diagnostic test, with sensitivity of 94% in AI diagnosis compared to other image tools (sensitivity of autofluorescence and photographic images of 89% and 91%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations